Longevity of Polish male Olympic medallists born between 1888 and 1965 - Malek, L. A.; Smigielski, W.; Krysztofiak, H.; Marszalek, M.; Drygas, W. (Biomedical Human Kinetics, 2021)
Study aim: The aim of the study was to analyse the lifespan of Polish male Olympic medallists in comparison to the general male population. Material and methods: The study included 238 Polish male Olympic medallists who participated in the Olympic games in 1924-1992. Duration of life in relation to the general Polish population was assessed. The age of acquiring their first medal, type and number of medals won and sports discipline were taken into consideration. Results: Polish male Olympic medallists born before 1940 lived over 8 years longer in comparison to the general population (p < 0.0001, d = 0.689 and d = 0.750). Over 80% of them lived up to 65 years of age and over 40% up to 80. In the general population only <70% and <30%, respectively, reached the equivalent lifespan (p = 0.010 and p = 0.040, RR = 0.480 and RR = 0.783). Kaplan-Meier analysis demonstrated that survival was shorter in Olympic medallists who won their first medal before the age of 25 (p = 0.040) and in those engaging in endurance or power sports vs. mixed or skill disciplines (p = 0.010). Conclusions: Polish male Olympic medallists lived significantly longer than the general population of Polish men. The longev-ity of male Olympic medallists was affected by the age of acquiring their first medal and by the category of sport practised